2013
DOI: 10.1124/dmd.113.054478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Mechanistic Analysis of the Cytotoxicity of the Acyl Glucuronide of Nonsteroidal Anti-Inflammatory Drugs

Abstract: The chemical reactivity of acyl glucuronide (AG) has been thought to be associated with the toxic properties of drugs containing carboxylic acid moieties, but there has been no direct evidence showing that AG formation is related to the observed toxicity. In the present study, the cytotoxicity of AGs, especially that associated with the inflammatory response, was investigated. The changes in the mRNA and protein expression levels of interleukin 8 (IL-8) and monocyte chemoattractant protein (MCP)-1 induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…With direct toxicity, covalent protein binding via acyl-glucuronide may disrupt the normal physiologic function of a critical protein or some critical regulatory pathway that leads to cellular necrosis (Pirmohamed et al, 1996). Inflammation-mediated toxicity was investigated in a recent study, which showed that acyl-glucuronides induce inflammatory toxicity and cytotoxicity against CD14 + cells via the p38 mitogen-activated protein kinase pathway (Miyashita et al, 2014). In the case of diclofenac, it was previously demonstrated that the acylglucuronide can either bind directly to protein with displacement of the glucuronide group, or can rearrange to form a reactive imine intermediate that binds to proteins (Kretz-Rommel and Boelsterli, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…With direct toxicity, covalent protein binding via acyl-glucuronide may disrupt the normal physiologic function of a critical protein or some critical regulatory pathway that leads to cellular necrosis (Pirmohamed et al, 1996). Inflammation-mediated toxicity was investigated in a recent study, which showed that acyl-glucuronides induce inflammatory toxicity and cytotoxicity against CD14 + cells via the p38 mitogen-activated protein kinase pathway (Miyashita et al, 2014). In the case of diclofenac, it was previously demonstrated that the acylglucuronide can either bind directly to protein with displacement of the glucuronide group, or can rearrange to form a reactive imine intermediate that binds to proteins (Kretz-Rommel and Boelsterli, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is increasing evidence that AGs form drug-protein adducts due to their chemical reactivity (Wang et al, 2001;Horng and Benet, 2013), cytotoxicity and genotoxicity of AGs have not been observed in vitro (Koga et al, 2011). Conversely, the AGs of withdrawn drugs and warning drugs that have idiosyncratic drug toxicity risks, such as zomepirac and diclofenac, induced the mRNA expression levels of immune-and inflammation-related genes in human PBMCs (Miyashita et al, 2014;Iwamura et al, 2015). Thus, these in vitro studies indicate that the toxicity of AGs remains controversial.…”
Section: Discussionmentioning
confidence: 97%
“…From our previous findings, AGs of warning and withdrawn drugs induced immune-and inflammation-related genes such as IL-6 and IL-8 in human PBMCs (Miyashita et al, 2014;Iwamura et al, 2015). Hence, the changes in the renal mRNA expression levels of immuneand inflammation-related genes were measured.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…9) It was therefore hypothesized that the trovafloxacin acyl-glucuronide was involved in the development of toxicity in the liver. Acyl-glucuronide-associated toxicity has been reported in vivo and in vitro ; 10,11) however, there are also reports showing that acyl-glucuronidation did not induce the cyto- and genotoxicity. 12) Microarray expression analysis is a promising tool to identify genes associated with a drug treatment.…”
Section: Introductionmentioning
confidence: 99%